2008
DOI: 10.4038/cjms.v48i2.122
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive hormones in seminal plasma; it's effect on semen quality

Abstract: The aim ofthis study was to investigate the effect of reproductive hormones in seminal plasma on the quality of the spermatozoa in men seeking infertility treatment. Of the 383 volunteers recruited, 123 had normal sperm parameters and 260 had either a single or a combination of sperm abno rmalities as per WHO criteria . Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH) Prolactin (PRL), Testosterone (T) and Estradiol (E2) levels in serum and semen of these men were determ in ed using an immunometri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The study subjects were assigned in to two groups: Normozoospermics and pathozoospermics based on the sperm parameters (WHO 2010) and comparisons were made in the two groups under the following, a) exposure to environmental and occupational reproductive toxicants and semen parameters b) exposure to environmental and occupational reproductive toxicants and presence of lead and cadmium in seminal plasma and c) the presence of lead and cadmium in seminal plasma and semen parametersIn the total population there were 99 (33%) pathozoospermics and 201 normozoospermics (67%). Similar previos studies carried out in Sri Lanka in different regions report that approximately 55-60% were pathozoospermics and 40%-45% were normozoospermics (219) (220)(221). The difference in the results obtained in current study and previous studies was due to the changes resulting in lower limits of the sperm parameters in WHO reference ranges on which normozoospennics and pathozoospermics are categorised.…”
supporting
confidence: 68%
“…The study subjects were assigned in to two groups: Normozoospermics and pathozoospermics based on the sperm parameters (WHO 2010) and comparisons were made in the two groups under the following, a) exposure to environmental and occupational reproductive toxicants and semen parameters b) exposure to environmental and occupational reproductive toxicants and presence of lead and cadmium in seminal plasma and c) the presence of lead and cadmium in seminal plasma and semen parametersIn the total population there were 99 (33%) pathozoospermics and 201 normozoospermics (67%). Similar previos studies carried out in Sri Lanka in different regions report that approximately 55-60% were pathozoospermics and 40%-45% were normozoospermics (219) (220)(221). The difference in the results obtained in current study and previous studies was due to the changes resulting in lower limits of the sperm parameters in WHO reference ranges on which normozoospennics and pathozoospermics are categorised.…”
supporting
confidence: 68%
“…found that seminal levels of PRL did not differ between normozoospermic and teratozoospermic men. On the contrary, Wijeratna et al [ 34 ] reported that there was a significant negative relationship between seminal PRL levels and sperm morphology. In vitro incubation of human spermatozoa in the presence of PRL increases motility and decreases DNA damage in a dose-dependent manner [ 13 ] and stimulates cell metabolism [ 10 ].…”
Section: Discussionmentioning
confidence: 98%
“…The seminal plasma, the liquid component of semen, consists of secretions from testes, epididymis, and the accessory sex glands, contains a variety of factors (amino acids, fatty acids, asmolytes and proteins) that influence the viability and fertilizating capacity of ejaculated spermatozoa (Mann and Lutwak-Mann, 1981;1990;Yanagimachi, 1994;Goericke et al, 2015). As seminal plasma is the immediate environment of spermatozoa, the substances in the seminal plasma could be expected to have profound effect on the quality of the sperm (Wijeranta et al, 2005). Seminal plasma was reported to be important for maintaining spermatozoa motility in bull (Baas et al, 1983).…”
Section: Introductionmentioning
confidence: 99%